Markov filtration of digital signals in residue number system - Valeriy Andreevich Pesoshin; Nataliya Andreevna Galanina; Nadezhda Nikolaevna Ivanova (Наука. Инновации. Технологии)
The article deals with signal processing algorithms, which are approximated by Markov chains on a background noise of Markov type. It is shown that the implementation of this algorithm requires significant hardware costs. Proposed to reduce them by using a residua number system (RNS). It is shown that this method of implementation, the processing of Markov signals can significantly reduce hardware expenses.